Adsorption of diclofenac from aqueous solution by amine-functionalized poly(Acrylonitrile-Co-Acrylic Acid) microparticles adsorbent - Zakira Amalin Mohamad,; Siti Nurul Ain Md Jamil,; Nur Nida Syamimi Subri,; Farhana Syakirah Ismail,; Rusli Daik, (Penerbit Universiti Kebangsaan Malaysia, 2023)
In this study, the synthesis of poly(acrylonitrile) (PAN) and poly(acrylonitrile-co-acrylic acid) (poly(ACN-co-AAc)) was carried out via redox polymerization, using sodium bisulphate (SBS) and potassium persulphate (KPS) as initiators. Subsequently, the resulting poly(ACN-co-AAc) was functionalized with ethanolamine (ETA) and ethylenediamine (EDA) to utilize as adsorbents for the removal of diclofenac from an aqueous solution. Both unfunctionalized and functionalized poly(ACN-co-AAc) were characterized using Fourier-Transform Infrared (FTIR) spectroscopy, Scanning Electron Microscope (SEM), Thermogravimetric Analysis (TGA), and Brunauer-Emmett-Teller (BET) analysis. The effects of pH, initial concentration of diclofenac solution, contact time, and adsorbent dosage were investigated during the adsorption process. The isotherm data were best fitted by the Langmuir model, indicating a mono-layered adsorption mechanism. The maximum adsorption capacities obtained from the Langmuir equation were higher for ETA-functionalized poly(ACN-co-AAc) at 120.5 mg/g, as compared to EDA-functionalized poly(ACN-co-AAc) at 80.6 mg/g. The experimental kinetic results showed that the pseudo-second-order model was a good fit for describing the adsorption rate of diclofenac for both ETA-functionalized poly(ACN-co-AAc) and EDA-functionalized poly(ACN-co-AAc), with R2 values of 0.9930 and 0.9906, respectively. This suggests that the chemisorption process is more favourable for the adsorption of diclofenac when using both types of adsorbents.